Reflections on Constitutional and Other Issues Concerning our Electoral System: the Past and the Future - Wallace, Sir John (Victoria University of Wellington Law Review, 2002)
The author, who served as the Chair of the Royal Commission on the Electoral Systems and the President of the Electoral Commission, reflects on New Zealand's change in voting system from First-Past-the-Post to Mixed Member Proportional (MMP) while providing his personal opinions. The article covers the appointment of Commissioners for the Royal Commission and the process in which MMP was chosen by the Commission. The author then discusses the various topics of debate under the MMP system including whether the introduction of a significant constitutional change should require more than a simple majority, how businesses and politicians reacted to the MMP system, whether MMP would lead to a weaker and fragmented government structure, whether MMP would give minor parties too much power, New Zealand's list MP system, voters' worries over "party hopping" during a government term, the need to provide effective Māori representation, number of MPs, the five percent threshold to get into Parliament, Parliamentary terms, and political finance. The author expresses pleasure that MMP obtained a greater degree of support than anticipated, and provides a number of talking points for democracy going forward.